Longitudinal clinical, cognitive and biomarker profiles in dominantly inherited versus sporadic early-onset Alzheimer’s disease - Llibre Guerra, Jorge J. (2023)
Approximately 5% of Alzheimer’s disease cases have an early age at onset (<65 years), with 5–10% of these cases attributed to dominantlyinherited mutations and the remainder considered as sporadic. The extent to which dominantly inherited and sporadic early-onsetAlzheimer’s disease overlap is unknown. In this study, we explored the clinical, cognitive and biomarker profiles of early-onsetAlzheimer’s disease, focusing on commonalities and distinctions between dominantly inherited and sporadic cases. Our analysis included117 participants with dominantly inherited Alzheimer’s disease enrolled in the Dominantly Inherited Alzheimer Network and 118 individualswith sporadic early-onset Alzheimer’s disease enrolled at the University of California San Francisco Alzheimer’s Disease ResearchCenter. Baseline differences in clinical and biomarker profiles between both groups were compared using t-tests. Differences in the ratesof decline were compared using linear mixed-effects models. Individuals with dominantly inherited Alzheimer’s disease exhibited an earlierage-at-symptom onset compared with the sporadic group [43.4 (SD ± 8.5) years versus 54.8 (SD ± 5.0) years, respectively, P < 0.001].Sporadic cases showed a higher frequency of atypical clinical presentations relative to dominantly inherited (56.8% versus 8.5%, respectively)and a higher frequency of APOE-ϵ4 (50.0% versus 28.2%, P = 0.001). Compared with sporadic early onset, motor manifestationswere higher in the dominantly inherited cohort [32.5% versus 16.9% at baseline (P = 0.006) and 46.1% versus 25.4% at last visit (P =0.001)]. At baseline, the sporadic early-onset group performed worse on category fluency (P < 0.001), Trail Making Test Part B (P <0.001) and digit span (P < 0.001). Longitudinally, both groups demonstrated similar rates of cognitive and functional decline in the earlystages. After 10 years from symptom onset, dominantly inherited participants experienced a greater decline as measured by ClinicalDementia Rating Sum of Boxes [3.63 versus 1.82 points (P = 0.035)]. CSF amyloid beta-42 levels were comparable [244 (SD ± 39.3)pg/ml dominantly inherited versus 296 (SD ± 24.8) pg/ml sporadic early onset, P = 0.06]. CSF phosphorylated tau at threonine 181 levelswere higher in the dominantly inherited Alzheimer’s disease cohort (87.3 versus 59.7 pg/ml, P = 0.005), but no significant differences werefound for t-tau levels (P = 0.35). In summary, sporadic and inherited Alzheimer’s disease differed in baseline profiles; sporadic early onset isbest distinguished from dominantly inherited by later age at onset, high frequency of atypical clinical presentations and worse executiveperformance at baseline. Despite these differences, shared pathways in longitudinal clinical decline and CSF biomarkers suggest potentialcommon therapeutic targets for both populations, offering valuable insights for future research and clinical trial design.